2022
DOI: 10.1002/jmv.28284
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative incidence of SARS‐CoV‐2 infection in the general population of the Valencian Community (Spain) after the surge of the Omicron BA.1 variant

Abstract: Studies investigating the cumulative incidence of and immune status against SARS‐CoV‐2 infection provide valuable information for shaping public health decision‐making. A cross‐sectional study on 935 participants, conducted in the Valencian Community (VC), measuring anti‐SARS‐CoV‐2‐receptor binding domain‐RBD‐total antibodies and anti‐Nucleocapsid (N)‐IgGs via electrochemiluminescence assays. Quantitation of neutralizing antibodies (NtAb) against ancestral and Omicron BA.1 and BA.2 variants and enumeration of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
4
11
2
Order By: Relevance
“…Our study also found that the correlate of infection-induced seroprevalence only, i.e., anti-N antibodies, decreased with age. This age-related finding is in accordance with post-BA.1 seroprevalence studies: children, adolescents, and young adults were the least vaccinated but most infected age subgroups during the Omicron BA.1 wave [ 28 , 29 , 32 , 34 , 35 , 43 ]. In most countries, the education systems functioned with few restrictions during this period, and children and adolescents were socialising to almost the same extent as before the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…Our study also found that the correlate of infection-induced seroprevalence only, i.e., anti-N antibodies, decreased with age. This age-related finding is in accordance with post-BA.1 seroprevalence studies: children, adolescents, and young adults were the least vaccinated but most infected age subgroups during the Omicron BA.1 wave [ 28 , 29 , 32 , 34 , 35 , 43 ]. In most countries, the education systems functioned with few restrictions during this period, and children and adolescents were socialising to almost the same extent as before the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…Anti-SARS-CoV-2 nucleocapsid protein (N) IgG antibodies and anti-RBD total antibodies were measured by the Elecsys ® Anti-SARS-CoV-2 N IgG assay and the Elecsys ® Anti-SARS-CoV-2 S assay (Roche Diagnostics), as previously reported. 17 NtAbs against Omicron BA.2 and BA4/5 were measured using a GFP-expressing vesicular stomatitis virus pseudotyped with the Omicron BA.2 and BA.4/5 S protein, as described elsewhere. [18][19][20]…”
Section: Antibody Assaysmentioning
confidence: 99%
“…A total of 50 individuals (median age, 44.5 years; range, 11-85; 25 males) randomly selected from 931 participants among the general population recruited in a SARS-CoV-2 cumulative incidence study conducted at the Valencian Community (Spain) in April, 2022 were included in the study. 21…”
Section: Study Populationmentioning
confidence: 99%